End-of-Life Care for Dying Peacefully in the Thai Buddhist Culture: Family Members’ and Nurses’ Perspectives - Sirilak Somanusorn (Prince of Songkla University, 2016)
Thesis (Ph.D., Nursing)--Prince of Songkla University, 2010